The Political Economy of Delaying Fiscal Consolidation - Cournède, Boris (OECD Publishing, 2007)
Over the next decades, many OECD countries are anticipating large increases in public spending as a result of population ageing and other long-term structural trends. The need to put public finances on a sustainable footing is widely recognised, but progress has been uneven and slow. Some policy makers may feel that action can be deferred for a few years at little cost because of the long-term nature of the problem. This paper questions this perception by proposing a model of the political costs of consolidating public finances. The main finding is that even a short delay increases political cost of consolidation quite markedly when ultimately policy makers are facing a deadline by which sustainability must be restored. The conclusion is very robust to changes in assumptions and specification. A variant of the model shows that with an infinite horizon the incentive to consolidate is weaker, which highlights the importance of setting a deadline. This paper relates to the 2007 Economic Survey of the Euro area (www.oecd.org/eco/surveys/euroarea)
Keywords: Economics